2011
DOI: 10.1017/s1368980011002175
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast consumption and daily physical activity in 9–10-year-old British children

Abstract: Objective: To examine the association between breakfast consumption and physical activity in a well-characterised sample of English children. Design: Cross-sectional study using food diaries to record breakfast consumption and accelerometry to assess physical activity. Setting: Norfolk county, England. Subjects: Children (n 1697) aged 9-10 years from the SPEEDY (Sport, Physical Activity and Eating behaviour: Environmental Determinants in Young people) study. Results: Boys who consumed a poor-quality breakfast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 42 publications
5
48
1
3
Order By: Relevance
“…These results were in line with earlier studies [20,24] and supported the finding that breakfast consumers tended to make healthier food choices throughout the day [25,26]. Although the association between breakfast consumption and physical activity was inconclusive [27,28,29], the present result suggested that students who ate breakfast sometimes or daily were more active than those who never did, especially for doing moderate physical activity and attending physical education classes. With regard to sedentary activity, our study found that students with daily breakfast consumption were less likely to use the computer more than two hours per day.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in line with earlier studies [20,24] and supported the finding that breakfast consumers tended to make healthier food choices throughout the day [25,26]. Although the association between breakfast consumption and physical activity was inconclusive [27,28,29], the present result suggested that students who ate breakfast sometimes or daily were more active than those who never did, especially for doing moderate physical activity and attending physical education classes. With regard to sedentary activity, our study found that students with daily breakfast consumption were less likely to use the computer more than two hours per day.…”
Section: Discussionsupporting
confidence: 92%
“…While some findings suggest sex is an effect modifier (34) , others do not (34,37) . While it is possible that the breakfast skipping-PA association differs for boys and girls, it is not likely that there is a biological explanation for this difference.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to a better overall quality of nutrition, studies suggest that the usual intake of breakfast is associated with a reduced risk of excess weight and reduced body mass index (BMI) in children and adolescents . This can mainly be attributed to the fact that children and adolescents who do not eat breakfast are less likely to have lunch and, or dinner regularly, tend to make poor food choices, consume unhealthy foods between meals, buy food outside home and be less physically active .…”
Section: Introductionmentioning
confidence: 99%